The EU Health Union in Search of a Definition and an Open Discussion - Agnes Sipiczki; Karel Lannoo (Intereconomics)
Abstract More than other EU ‘Unions’, the proposed Health Union requires proper definition because the EU’s competences are limited in this domain.